Mixed Convection in Ferrofluids Vertical Layer with Inclined Magnetic Field (Journal of Engineering Science, 2024)
In this article, the flow characteristics and linear stability of mixed convection in a ferrofluid layer are investigated. The fluid layer is positioned between two vertically oriented and differently heated nonmagnetic plates under an inclined magnetic field with non-zero gravity. This study involves the patterns of fluid motion, heat transfer, and the effects of the inclined magnetic field with gravitational action. The objective of this article is to analyze the flow characteristics of smaller Prandtl number of fluid and figure out the significant comparisons with larger Prandtl numbers of fluids. The characteristic of every instability mode is examined for a fluid having a different Prandtl number than the one that was previously investigated. The influence of buoyancy effects undergoes a notable transformation, shifting from a destabilizing role in flows dominated by gravity to a stabilizing role in flows characterized by stronger magnetic effects. It is found that in both normal and oblique magnetic fields, the basic flow evolves into a state of greater stability, and wave propagation is faster with lower Prandtl numbers of fluids than with larger Prandtl numbers of fluids.Journal of Engineering Science 14(2), 2023, 31-45